Sistem Monitoring Konsumsi Daya Listrik Dengan Mengimplementasikan Bluetooth Low Energy - Rahmadya, Budi Rahmadya (Universitas Andalas, 2021)
Electricity becomes a major need for human in this era. PLN's electricity payment system in residential areas is divided into two ways, postpaid electricity and prepaid electricity. Prepaid electricity using digital kWh meter that shows the use of current, electric power, etc on LCD. The usage of current and electric power can be monitored using Android application using Bluetooth Low Energy (BLE) as communication media. BLE has many advantages module compared to classic bluetooth, for example having a wider range, data transfer speeds up to 1 Mbps, and low power consumption. Therefore the writer researched by implementing Bluetooth Low Energy in the electric power monitoring system. The results of this research showed that the electric power monitoring system and the BLE module could send the result of sensor measurement to android applications. From the testing that has been done showed that the BLE send module can be up to 25 meters distance for unhindered conditions and 8 meters with hindered conditions. And the BLE module energy consumption is more efficient than HC-05 energy comparison BLE module 5,728 mW and the HC-05 module 13.47 mW.